Critical Process in Paddy Residue-Based Power Generation in Malaysia: Economic and Environmental Perspective - Mohd Shafie, Shafini; Othman, Zakirah; Hami, Norsiah (American Scientific Publishers, 2017)
Malaysia is one of the leading producers of paddy. It has reached 0.48 million metric tonnes of rice husk and 3.1 million metric tonnes of rice straw in a year due to the emerging technological development in agroindustry.The consumption of paddy residue (both rice husk and rice straw) in electricity generation creates a vast potential to explore. However, the generation of electricity from paddy residue faces various environmental, technological, and social challenges.This paper identifies the most critical processes in paddy residue-based power generation towards the environmental and economic impacts.The transportation process is the most critical part, where personnel cost is the most sensitive cost to this process.The rice husk electricity generation cost is RM0.6075/kWh and rice straw is RM0.2725/kWh.The overall process, beginning from the production of paddy residue until electricity generation, will be examined to find the critical process in paddy residue-based power generation. This paper can encourage the utilization of renewable energy, parallel to the government policy to move with green energy, and can serve as a guideline for policy makers in the implementation of more renewable energy in Malaysia.